2021
DOI: 10.1093/alcalc/agaa136
|View full text |Cite
|
Sign up to set email alerts
|

Andrographis paniculata and Its Main Bioactive Ingredient Andrographolide Decrease Alcohol Drinking and Seeking in Rats Through Activation of Nuclear PPARγ Pathway

Abstract: Background and aims Andrographis paniculata is an annual herbaceous plant which belongs to the Acanthaceae family. Extracts from this plant have shown hepatoprotective, anti-inflammatory and antidiabetic properties, at least in part, through activation of the nuclear receptor Peroxisome Proliferator-Activated Receptor-gamma (PPAR γ). Recent evidence has demonstrated that activation of PPARγ reduces alcohol drinking and seeking in Marchigian Sardinian (msP) alcohol-preferring rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…ex Nees, can be used to treat cold, fever, sore throat, sore mouth and tongue (Jiang et al, 2013). In recent decades, with the increasing interest in the research of this phytomedicine, abundant of researches has proven that the intervention of modern novel technics to excavate the main effective components from it has become a hot spot (Patil & Jain, 2021; Stopponi et al, 2021). It has been reported that andrographolide (Figure 1), ((3E,4S)‐3‐[2‐[(1R,4aS,5R,6R,8aS)‐6‐hydroxy‐5‐(hydroxymethyl)‐5,8a‐dimethyl‐2‐methylidene‐3,4,4a,6,7,8‐hexahydro‐1H‐naphthalen‐1‐yl]ethylidene]‐4‐hydroxyoxolan‐2‐one; PubChem CID: 5318517, CAS No.…”
Section: Introductionmentioning
confidence: 99%
“…ex Nees, can be used to treat cold, fever, sore throat, sore mouth and tongue (Jiang et al, 2013). In recent decades, with the increasing interest in the research of this phytomedicine, abundant of researches has proven that the intervention of modern novel technics to excavate the main effective components from it has become a hot spot (Patil & Jain, 2021; Stopponi et al, 2021). It has been reported that andrographolide (Figure 1), ((3E,4S)‐3‐[2‐[(1R,4aS,5R,6R,8aS)‐6‐hydroxy‐5‐(hydroxymethyl)‐5,8a‐dimethyl‐2‐methylidene‐3,4,4a,6,7,8‐hexahydro‐1H‐naphthalen‐1‐yl]ethylidene]‐4‐hydroxyoxolan‐2‐one; PubChem CID: 5318517, CAS No.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, peroxisome proliferator-activated receptor-gamma (PPARγ) agonism has been shown as a new strategy to address alcohol use disorder (AUD) and possibly to other addictive substances [ 129 ]. The administration of A. paniculata extract or andrographolide activates the transcription factor PPARγ [ 130 ].…”
Section: Miscellaneous Natural Productsmentioning
confidence: 99%
“…Optical microscopy: Formulated phyto-phospholipid complexes were viewed under the microscope, a drop of suspension formed was taken on a glass slid and excess of suspension was drained off with filter paper and was allowed to dry. The Sample formed was then viewed under optical microscope to visualize the vesicle formation (6).…”
Section: Preparation Of Phyto-phospholipid Complexesmentioning
confidence: 99%